Source data for "Highly polarized electrically driven single-photon emission from a non-polar InGaN quantum dot" - Kocher, C; Puchtler, T; Jarman, J; Zhu, T; Wang, T; Nuttall, L; Oliver, R; Taylor, R (University of Oxford, 2017)
Creation: 11.2016-1.2017 Raw data + analysed data by Matlab and Origin For each figure the rawdata underlying it was added as well.